2018
DOI: 10.1088/2515-7639/aaf263
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the ex vivo permeation behaviour of functionalised contact lens coatings engineered using an electrohydrodynamic technique

Abstract: In vitro testing alone is no longer considered sufficient evidence presented solely with respect to drug release and permeation testing. These studies are thought to be more reliable and representative when using tissue or animal models; as opposed to synthetic membranes. The release of anti-glaucoma drug timolol maleate from electrically atomised coatings was assessed here using freshly excised bovine corneal tissue. Electrohydrodynamic processing was utilised to engineer functionalised fibrous polyvinylpyrro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
0
8
0
1
Order By: Relevance
“…By using a special mixing ratio of permeation enhancers and polymers, Mehta et al (2018) presented the capability of utilizing electrohydrodynamic atomization (EHDA) in engineering strong coverings to improve the permeation of pharmaceuticals, thus increasing the bioavailability of ocular drugs ( Supplementary Table S5 ). Their ex vivo analyses indicated that by adding permeation enhancers, a substantial increase in TM permeation in comparison to an additive-free setup could be achieved (53.39 ± 3.95 μg cm − 2 ) after 24 h. This significant improvement in drug permeation resulted in a decline in ocular toxicity due to the lower systematic absorption over an appropriate time frame [ 27 ].…”
Section: Electrospun-fiber-incorporated Contact Lenses For Drug Deliverymentioning
confidence: 99%
See 2 more Smart Citations
“…By using a special mixing ratio of permeation enhancers and polymers, Mehta et al (2018) presented the capability of utilizing electrohydrodynamic atomization (EHDA) in engineering strong coverings to improve the permeation of pharmaceuticals, thus increasing the bioavailability of ocular drugs ( Supplementary Table S5 ). Their ex vivo analyses indicated that by adding permeation enhancers, a substantial increase in TM permeation in comparison to an additive-free setup could be achieved (53.39 ± 3.95 μg cm − 2 ) after 24 h. This significant improvement in drug permeation resulted in a decline in ocular toxicity due to the lower systematic absorption over an appropriate time frame [ 27 ].…”
Section: Electrospun-fiber-incorporated Contact Lenses For Drug Deliverymentioning
confidence: 99%
“…Scientists have created a range of fiber networks to focus on both drug delivery and the engineering of corneal tissue. One of the main challenges when dealing with electrospun fibers for drug loading and release is the fine-tuning of the fiber matrix and its morphology, porosity, and wettability, as drug particles may get trapped within the network of fibers, which may act as barriers to hinder the drug diffusion instead of promoting it [ 22 , 26 , 27 ]. Furthermore, the low efficacy and systemic side effects of these electrospun release systems are additional aspects to be thoroughly studied [ 143 ].…”
Section: Limitations and Existing Challenges Of The Contact Lensesmentioning
confidence: 99%
See 1 more Smart Citation
“…chitosan [152][153][154][155][156], collagen [157][158][159][160], SF [161][162][163][164], gelatin [165][166][167][168][169][170]) and synthetic polymers (e.g. PGA [171][172][173], poly lactic acid (PLA) [174][175][176][177][178][179], PLGA [180][181][182][183][184][185][186][187][188], poly vinylpyrrolidone (PVP) [77,[189][190][191][192][193][194], PCL [195][196][197][198][199][200]<...…”
Section: Electrospinningunclassified
“…This topical review highlights progress with different functional stimuli based on molecular design, with prospective comments on their future in health application. Keeping with the advanced biomaterials design for medical therapeutics, our next original article by Mehta et al [2], De Montfort University, United Kingdom, describes the development of a new fibrous coating on tissue via electrohydrodynamic technique, which is applicable for ex vivo drug testing model. Another interesting contribution is from Konishi et al [3] who investigated the effects of an amorphous hydrated layer in bioceramics fabrication using nuclear magnetic resonance spectroscopy.…”
Section: Introductionmentioning
confidence: 99%